Nota sobre Hanseniella sp. (Symphyla), praga de arroz (Oryza sativa L.) em Viçosa, Minas Gerais - Camargos Loureiro, Milgar; Domingos Galvão, José (Revista Ceres, 2025)
Hanseniella sp. (Symphyla) was observed for the first time inBrazilas a pest of rice. Specimens were found in Vigosa, inthe State of Minas Gerais causing injury to the coleoptile and radicle of rice seedlings grown with sprinkler irrigation. As a consequence, the emergence was reduced around 90 percent.